Use of the CDR® plus NACC FTLD in mild FTLD: Data from the ARTFL/LEFFTDS consortium. Issue 1 (6th January 2020) - Miyagawa, Toji; Brushaber, Danielle; Syrjanen, Jeremy; Kremers, Walter; Fields, Julie; Forsberg, Leah K.; Heuer, Hilary W.; Knopman, David; Kornak, John; Boxer, Adam; Rosen, Howie; Boeve, Bradley; et al.
Abstract: Introduction: Behavior/Comportment/Personality (BEHAV) and Language (LANG) domains were added to the Clinical Dementia Rating (CDR®) for improving evaluation of patients with frontotemporal lobar degeneration (FTLD) (CDR® plus NACC FTLD). Methods: We analyzed the CDR® plus NACC FTLD among participants from the baseline visit of the Advancing Research and Treatment for Frontotemporal Lobar Degeneration/Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects Consortium. Results: The CDR® plus NACC FTLD was able to detect early symptoms in the mildly impaired participants who were rated as CDR® sum of boxes (CDR®‐SB) = 0. The CDR®‐SB was not sensitive, particularly in participants with mild nonfluent/agrammatic primary progressive aphasia. Participants with familial and sporadic behavioral variant FTD exhibited similar CDR® plus NACC FTLD profiles except that language impairment was more frequent in participants with mild sporadic behavioral variant FTD. Adding the BEHAV and/or LANG domains to the CDR®‐SB significantly enhanced discriminatory power in differentiating among the FTLD spectrum disorders. Discussion: The BEHAV and LANG domains enable the CDR® plus NACC FTLD to capture early symptomatology of FTLD.